Perubahan Pola Komunikasi Keluarga di Era Digital: Antara Keterhubungan dan Keterasingan - Latifah, Alfira Nurul; Rahayu, Ika Puji; Oralas, Indira (Lentera Ilmu Madani, 2025)
The development of digital technology has significantly changed communication patterns in families. This study aims to systematically analyze changes in family communication in the digital era with a focus on two main dimensions: emotional connectedness and alienation. This study uses the Systematic Literature Review (SLR) method based on the PRISMA guidelines. The selection process was carried out on 72 initial articles found through Google Scholar, by applying certain inclusion criteria. After a full selection and review process, 10 scientific articles published in 2023–2025 were further analyzed. The synthesis results show five main findings: (1) the shift in family communication from face-to-face interactions to digital communication based on applications and social media; (2) digital media plays a dual role as a bridge of connectedness as well as a potential cause of emotional alienation; (3) the role of parents as mediators is crucial in shaping the quality of digital family communication; (4) emotional presence has more impact than just the frequency of online communication; and (5) the need for healthy, reflective, and adaptive family communication strategies to maintain harmony in the digital environment. This review also reveals the dominance of qualitative approaches in previous studies and recommends the development of quantitative and mixed methods approaches for further research. Overall, the effectiveness of digital communication in families is not only determined by the technology used, but primarily by the values, relationships, and awareness of communication within the family structure itself.